ANALISIS PENGARUH MOTIVASI WISATAWAN TERHADAP MINAT BERKUNJUNG WISATAWAN KE SUKU BADUY, BANTEN - Goutama, Serley Anggraini; Sri Puspadewi, Roels Ni Made (Program Studi Hospitality dan Pariwisata, 2024)
Tourism activities can be said to have existed since humans were on earth, where humans moved from one place to another. The meaning of tourism itself varies greatly according to the history and geography of movement behavior, because the behavior of moving places cannot be separated from various motivations or encouragement from within the human being himself. This study aims to measure the motivation for visiting tourists to the Baduy Tribe, Banten. The type of research used in this study is quantitative. Methods of data collection using questionnaires and observations. The total respondents in this study were 100 tourists who had visited the Inner Baduy Tribe with the sampling technique using Purposive Sampling. The analytical method used in this study uses simple linear regression analysis and descriptive statistical tests. Based on the results of the test of the coefficient of determination, the results obtained are that motivation influences the interest of visiting tourists by 40.2% and the rest is influenced by other variables. Based on the hypothesis test, it shows a significant value of 0.000, which means that motivation influences the interest in visiting tourists to the Baduy tribe.